PENERAPAN KNOWLEDGE MANAGEMENT: ORAL HISTORY PENANGANAN ARSIP BENCANA TOPAN HAIYAN DI FILIPINA - Riyadi, Aris; Mahmudah, Afdini; Utami, Diah (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2016)
Knowledge management process using Nonaka’s SECI model in creation of knowledge can provide guidance for learning and developing activities. Nevertheless, understanding the process of socialization, externalization, combination and internalization needs to be deepened with a lot of practice directly. This article provides a framework for real method that synthesizes basic phases as informal knowledge from an expert who has never capture and promotes knowledge before. Purpose of this article is to open earlier tacit knowledge form into process of socialization and internalization. An expert knowledge how to handling damage records by natural disaster will revealed in explicit way through capture process of oral history. Process for document damage recovery is conducted using disaster management procedure or library materials preservation knowledge. Research method for knowledge capture carried through pre-interview, interview and post-interview. Support data such as form of images, diaries, letters, agreements and others are used to reinforce methodology. Applying this method will produce two knowledge directly which are disaster management knowledge and management knowledge processes.